THE ECONOMIC AND CAREER EFFECTS OF SEXUAL HARASSMENT ON WORKING WOMEN - MCLAUGHLIN, HEATHER (Gend Soc, 2017)
Many working women will experience sexual harassment at some point in their careers. While some report this harassment, many leave their jobs to escape the harassing environment. This mixed-methods study examines whether sexual harassment and subsequent career disruption affect women’s careers. Using in-depth interviews and longitudinal survey data from the Youth Development Study, we examine the effect of sexual harassment for women in the early career. We find that sexual harassment increases financial stress, largely by precipitating job change, and can significantly alter women’s career attainment.